The penguin problem - Klein, Abby.; McKinley, John, 1956- (New York : Scholastic, 2010)
Freddy's first grade class is learning all about penguins. When the class discovers some are endangered, they want to help. Can Freddy come up with a good plan to save the penguins?
"Little apple"
Keywords: Endangered species -- Juvenile fiction; Penguins -- Juvenile fiction; First grade (Education) -- Juvenile fiction; Endangered species -- Fiction; Penguins -- Fiction; Schools -- Fiction